PERSPEKTIF ISLAM TENTANG MODERASI BERAGAMA: ANALISIS TAFSIR MAUDHU’I - Maulida Fatihatusshofwa; Muhammad Haekal Fatahillah Akbar; Muhammad Hamzah Nashrullah (Melati Institute, 2023)
The discourse on freedom and religious diversity in Indonesia has long been highlighted by various elements of the state and scholars of the nation. Ultimately, the only solution found so far is by implementing the concept of moderation in practicing religion. This research aims to describe the essence of religious moderation from an Islamic perspective and serve as a reference and study for classic issues concerning the community and its beliefs. This research adopts the maudu’i (thematic) method, which is entirely qualitative in nature. The reference sources utilized in this study include both print and digital documents, such as books, journals, essays, and other relevant references. The research findings indicate that from an Islamic perspective, religious moderation means prioritizing a tolerant attitude towards differences and embracing diversity (inclusivism), whether it be diverse in terms of sects or schools of thought or diverse in terms of religious practices. In Indonesia, the existence of moderate religious thought has long been present. This can be evidenced by identifying several aspects. Firstly, the peaceful introduction of Islam to the archipelago; secondly, throughout history, renowned scholars have responded to the evolving dynamics of thought; and thirdly, Islamic figures have increasingly encountered a dynamic social construct that necessitates their efforts in constructing a society that responds to various evolving modernities.